2007
DOI: 10.1158/1535-7163.mct-06-0404
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity of sulforaphane in Akt-overexpressing ovarian cancer cells

Abstract: Epidemiologic studies show a correlation between increased consumption of fruits and vegetables with reduced risk of ovarian cancer. One major bioactive compound found in cruciferous vegetables, particularly broccoli, is sulforaphane, derived from the breakdown of glucoraphanin. We observed potent antiproliferative effects of sulforaphane on human ovarian cancer cell line SKOV3 (IC 50 40 Mmol/L) and mouse ovarian cancer cell lines C3 and T3 (IC 50 25 Mmol/L each) by cell viability assays. The loss of viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 29 publications
3
65
1
Order By: Relevance
“…This pathway is particularly important in the drug response of tumor cells, such as ovarian cancer, that display activation of AKT and other components or low expression of tumor suppressors (e.g. PTEN, a Pi3K/AKT cascade regulator) (31,42). AKT activity has been shown to correlate with poor prognosis in patients suffering ovarian cancer (43).…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is particularly important in the drug response of tumor cells, such as ovarian cancer, that display activation of AKT and other components or low expression of tumor suppressors (e.g. PTEN, a Pi3K/AKT cascade regulator) (31,42). AKT activity has been shown to correlate with poor prognosis in patients suffering ovarian cancer (43).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treatment with 8 μM sulforaphane for 72 h effectively reduced growth (by 50%) of the ovarian cancer cell lines MDAH 2774 and SKOV3 [19]. A previous study demonstrated that sulforaphane effectively suppresses the growth of human and mouse ovarian cancer cells that overexpress AKT [12]. In our study, the growth-inhibitory effect of sulforaphane was also observed in OVCAR4 and OVCAR5 cells that express low levels of AKT, in addition to OVCAR3 and SKOV3 cells that express high levels of AKT [14].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of sulforaphane inhibits and/or retards tumorigenesis induced by carcinogens in animal models [10,11]. In addition to its preventive effect on cancer, sulforaphane has recently been shown to inhibit the growth of various types of cancer cells by modulating multiple pathways related to cancer progression [7,12]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, activation of the PI3K pathway serves to repress FOXO-mediated growth arrest and apoptosis. SFN has been shown to downregulate PI3K/ AKT (26,27) pathways in vitro. Furthermore, we have recently demonstrated that SFN can inhibit the phosphorylation (activation) of AKT in human prostate cancer cells orthotopically implanted in nude mice (9).…”
Section: Introductionmentioning
confidence: 99%